dengan,terhadap,pada PENGARUH METODE BERMAIN PERAN DENGAN MEDIA BONEKA TANGAN TERHADAP KEMAMPUAN BERBICARA PADA SISWA TK (4-5 tahun) Budhiyasa Sangsit - Putu Windi Ridayanti; Kadek Devy Marleni; Ni Nyoman Laras Sintya Dewi (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2020)
Introduction: Hand puppets are puppets used as media or tools used in learning activities. The type of doll that is usually used is a hand puppet made of pieces of cloth. The purpose of this study was to determine the effect of the role playing method with hand puppet media on the speaking ability of children aged 4-5 years at Budhiyasa Kindegardeen. Method: The study design used pre-experimental design with one group pre-post test design. The population used in this study were children aged 4-5 years at Budhiyasa Kindegardeen.. The sample size used is 30 respondents who have been selected using the total sampling technique. Measurement of speech ability was collected using an observation sheet guided by assignments according to age in Denver II. This study uses parametric statistics using the Paired Sample T-test with a significant level of α = 0.05. Results: The results showed the mean (pre-test) was 56.00 and the post-test mean was 68.33. The results of parametric statistical tests using the Paired Sample T-test results obtained pre and post (0,000) <α (0.05), which means that H0 is rejected and Ha is accepted. Conclusion: This shows that there is an influence of the method of playing the role of the Denagan Media Hand Puppets on the ability to speak to children aged 4-5 years in Singaraja Telkom ECD.